Development of Contextual-Based Interactive Multimedia of Tema Daerah Tempat Tinggalku of 4th Grade Students in Public Elementary School (SDN) 054919 Kacangan, Secanggang District, Langkat Regency - Fifit Sahputra; Restu Restu; Mursid Mursid (BIRCU, 2019)
This study aims to develop contextual-based interactive multimedia of Tema Daerah Tempat Tinggalku. This research is conducted at SDN 054919 Kacangan, Secanggang District, Langkat Regency. The population in this study are 4th grade students consisting of 30 students. The instruments which is used in this study are social studies learning outcomes tests and student response questionnaires. The data are collected and analyzed by quantitative descriptive analysis techniques. The method of this research is the development of Borg & Gall research combined with the learning development model of Dick & Carey. The trial subjects consists of learning material experts, learning design experts, two instructional media design experts, three students for individual trials, six students for small group trials and thirty students for large group trials. The results of the study show (1) The results of the trial of subject matter experts in the assessment of the content and feasibility of presentation are in very good criteria (88.09%); (2) The results of the learning design expert's test are in very good criteria (85.42%); (3) The results of the expert design study media I test are in sufficient criteria (73.21%) while the expert design test results of learning media II are on the sufficient criteria (83.92%); (4) The results of individual trials are in very good criteria (81.67%); (5) The results of the small group trial are in very good criteria (90.42%); (6) The results of a large group trial are in the criteria of good (73.2%).